THE EFFECTS OF ELECTROMAGNETIC RADIATION (954 KHZ) ON THE PEOPLE’S HEALTH, LIVING NEAR THE HIGH POWER RADIO BROADCASTING ANTENNA - ARVIND KUMAR; VIJAY KUMAR; P. P. PATHAK (International Journal of Pharma and Bio Sciences, 2014)
The harmful effects from exposures due to non-ionizing electromagnetic energy of intermediate frequency radiation were studied for the people who are living near radio tower of frequency 954 kHz. The AM radio broadcast (All India radio) towers radiate the electromagnetic energy in atmosphere, which can affect the health of human beings. The penetrated electric fields and specific absorption rate (SAR) inside the human body tissues are calculated by various parameters such as skin depth, conductivity and permittivity of tissues. The penetrated electric fields and specific absorption rate (SAR) inside the selected tissues are calculated at various distances from antenna and compared with the given permissible limit by the international agencies as international communication of non-ionizing radiations and protection (ICNIRP), world health organizations (WHO) etc. The result suggested that EMWs of given frequencies are harmful for the tissue life of the human body at various distances from the All India radio tower.